Analysis of Forward Anti-Plane Elastodynamic Problem in an Infinite Medium using Boundary Integral Equation Method - Neny Kurniasih (Institut Teknologi Bandung, 2010)
The anti-plane elastodynamic problem could be governed mathematically and expressed by the linear second-order partial differential equation. With the aid of the dynamic reciprocal theorem, the differential equation is transformed into an equivalence integral one. The evaluation of singular integral is performed analytically while the nonsingular one is calculated numerically using the standard Gaussian quadrature. As numerical implementations, boundary solutions are investigated for an infinitely long cavity with various cross sections due to various angles of incident wave. The method is applied for various spatial and time elements.